2020
DOI: 10.1364/ome.410081
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical properties linked to laser damage behavior in conductive thin film materials

Abstract: Epsilon-near-zero-materials (ENZ-materials) and their unique properties are key to the successful integration and miniaturization of optical components. Novel concepts, which promise significant progress in this field of research, such as optical switches and thin film electro-optical modulators, are possible when the electrical and optical properties of ENZ-materials are carefully exploited. To achieve a greater understanding of these properties, in this paper the electrical conductivity, optical transmittanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…This suggests that the origin of these fractures is the heat stress caused by the rapid heating of the laser-treated area due to the absorbed energy of the laser pulses. This is also supported by similar observations of Steinecke et al when annealing ITO at high temperatures [22]. Fig.…”
Section: Resultssupporting
confidence: 88%
“…This suggests that the origin of these fractures is the heat stress caused by the rapid heating of the laser-treated area due to the absorbed energy of the laser pulses. This is also supported by similar observations of Steinecke et al when annealing ITO at high temperatures [22]. Fig.…”
Section: Resultssupporting
confidence: 88%
“…It has to be noted, however, that the nonlinear effects in ITO can be of sufficient strength to exceed the assumption of small perturbations that is typically made in modeling nonlinear optics [18]. In addition to its strong nonlinear interaction with incident radiation, the intrinsic laser-induced damaged threshold (LIDT) of ITO is relatively high [19], which makes it ideal for the integration into KBS.…”
Section: Materials and Manufacturingmentioning
confidence: 99%
“…The remaining optical properties like absorption and LIDT were investigated in detail, too. It was found that they can be tuned in a wide range by post-process annealing to achieve various absorption and LIDT values [17].…”
Section: Coating Materials and Manufacturingmentioning
confidence: 99%